The Quality of Life of the Population of the Arctic Zone of Russia and Financial and Economic Mechanisms for Improving It from the Standpoint of Strengthening National Interests - GORDYACHKOVA, Olga V.; NIKULKINA, Inga V.; ROTAR, Tatiana S.; GRITSENKO, Sofya E.; FILIMONOVA, Lyudmila M. (Journal of Advanced Research in Law and Economics, 2019)
The study is devoted to the research of the quality of life of the population of the Arctic zone of Russia, which is one of the most important priorities of the socio-economic development strategy of the country. Based on the application of economic analysis methods, including correlation and regression modeling based on data for 2008–2017, modern trends and key factors were determined that affect the dynamics of the human development index, which is defined as an effective indicator that most fully and comprehensively reflects the quality of population life. The analysis revealed negative characteristics of the quality of life of the population of the Russian Arctic: income level that does not correspond to the level of needs, the higher unemployment rate in comparison with average data, lack of decent housing conditions, extremely insufficient infrastructure development level and low territory development. Applied correlation and regression modeling demonstrated that the main factors affecting the dynamics of the human development index are the pace of housing construction and crime rate. Given the complexity of these factors and revealed correlation with other factors, the results of analysis prove the need for an integrated approach to the development of the Arctic territories, in which the state plays the most important role through financial and economic mechanisms. Based on the study, an adapted set of financial and economic regulatory mechanisms aimed at the development of the Russian Arctic territories and improving the quality of life of the population of the Arctic zone of Russia was proposed